A Comparative Study of: the Allegorical and Symbolic Expression of Paradise and Hell in “Ardavirafname” and the Movie “What Dreams May Come” - Alireza Pourshabanan; Amir Hossein Pourshabanan (مطالعات زبانی و بلاغی)
The attention to the issue of post-death life is one of the things that, in the form of the parable of the narrative of the journey to heaven and hell, was created in the literary and artistic works of various nations throughout history, with regard to the cultural, social and religious factors of each society. The wishes and pains of human life in the other world have been exhibited. Adavirafname (narrative and prose) of Iranian literature and the movie "What Dreams May Come" is the product of American cinema, among which the allegorical journey to heaven and hell is depicted in them, and this paper attempts to analyze and answer the main question to about the allegory of this course and the function of the symbols in these works, what are the similarities and differences, and the reasons for these different interpretations in a descriptive way. This comparison shows that, given the dominant individualism of the movie, the symbolic expression in that narrow interpretation with a specific framework, focused on shaping the sensory relationship with the audience in the form of recreating scenes from heaven and hell personal, and emphasizing pleasures and spiritual sufferings and individual motivations, but in Ardavirafname, by emphasizing on the notions of collective memory and religious believes, symbols in the general form, repetitive interpretations and educational-religious goals, and focusing on physical rewards in the context of the general parable of the journey to heaven and hell, the main theme of the text has been shaped.